Outpatient total knee and hip arthroplasty present comparable and even better clinical outcomes than inpatient operation - Gong, Song; Yi, Yihu; Wang, Ruoyu; Han, Lizhi; Gong, Tianlun; Wang, Yuxiang; Shao, Wenkai; Feng, Yong; Xu, Weihua (Frontiers in Surgery, 2022)
Background The purpose of this study was to compare total complications, complications stratified by type, readmissions, and reoperations at 30 and 90 days after outpatient and standard inpatient total knee and total hip arthroplasty (TKA, THA). Methods A literature search was conducted from the PubMed, Cochrane Library, and Embase databases for articles published before 20 August 2021. The types of studies included prospective randomized controlled trials, prospective cohort studies, retrospective comparative studies, retrospective reviews of THA and TKA registration databases, and observational case-control studies. Comparisons of interest included total complications, complications stratified by type, readmissions, and reoperations at 30 and 90 days. The statistical analysis was performed using Review Manager 5.3. Results Twenty studies with 582,790 cases compared relevant postoperative indicators of outpatient and inpatient total joint arthroplasty (TJA) (TKA and THA). There was a significant difference in the total complications at 30 days between outpatient and inpatient THA (p = 0.001), readmissions following TJA (p = 0.03), readmissions following THA (p = 0.001), stroke/cerebrovascular incidents following TJA (p = 0.01), cardiac arrest following TJA (p = 0.007), and blood transfusions following TJA (p = 0.003). The outcomes showed an obvious difference in 90-day total complications between outpatient and inpatient TJA (p = 0.01), readmissions following THA (p = 0.002), and surgical-related pain following TJA (p < 0.001). We did not find significant differences in the remaining parameters. Conclusion Outpatient procedures showed comparable and even better outcomes in total complications, complications stratified by type, readmissions, and reoperations at 30 and 90 days compared with inpatient TJA for selected patients.